Measuring Belt and Road Initiative Perceptions: A Comparative Analysis of Thai Border and Non-Border Regions - Champahom, Thanapong; Chonsalasin, Dissakoon; Theerathitichaipa, Kestsirin; Jomnonkwao, Sajjakaj; Watcharamaisakul, Fareeda; Kasemsri, Rattanaporn; Ratanavaraha, Vatanavongs (Civil Engineering Journal, 2024)
This study aims to analyze and compare perceptions of the Belt and Road Initiative (BRI) between border and non-border regions in Thailand, addressing a gap in understanding how geographic proximity influences BRI project views. Using a sample of 3,200 respondents, this study employed confirmatory factor analysis and measurement invariance techniques to examine perceptions across eight key constructs related to BRI impacts. The findings reveal significant structural differences in BRI perceptions between border and non-border regions. Non-border regions generally showed more consistently positive perceptions across all constructs, while border regions demonstrated more varied and nuanced views. Notable differences were observed in perceptions of economic benefits, logistics improvements, and social impacts. This study contributes to the field by providing a comprehensive comparative analysis of BRI perceptions across different geographical contexts within a single country, employing advanced statistical methods to ensure valid comparisons. The results suggest the need for tailored approaches to BRI implementation and communication in different regions, implementing inclusive policy-making processes, and establishing robust monitoring and evaluation systems to address the varied perceptions and potential impacts of BRI projects in Thailand. Doi: 10.28991/CEJ-2024-010-12-010 Full Text: PDF